2012
DOI: 10.1152/advan.00056.2011
|View full text |Cite
|
Sign up to set email alerts
|

An international basic science and clinical research summer program for medical students

Abstract: An important part of training the next generation of physicians is ensuring that they are exposed to the integral role that research plays in improving medical treatment. However, medical students often do not have sufficient time to be trained to carry out any projects in biomedical and clinical research. Many medical students also fail to understand and grasp translational research as an important concept today. In addition, since medical training is often an international affair whereby a medical student/re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…Previous reports have described structured research opportunities that have contributed to the development of medical students' research skills. Whether nationally or internationally [21,22], it has been shown that a structured research education and modest funding are sufficient to help medical students build up their research knowledge and publish scientific work. Finally, given the condensed nature of medical curricula, adding a research methodology course may require removing another element from the curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have described structured research opportunities that have contributed to the development of medical students' research skills. Whether nationally or internationally [21,22], it has been shown that a structured research education and modest funding are sufficient to help medical students build up their research knowledge and publish scientific work. Finally, given the condensed nature of medical curricula, adding a research methodology course may require removing another element from the curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…In developing and under-developing countries (including Saudi Arabia), optimal implementation of curricular research training remains fairly unachievable by medical schools 4 , 5 . This problem is further compounded by the fact that extracurricular research activities remain largely unpopular by medical students.…”
Section: Introductionmentioning
confidence: 99%
“…Medical students also constitute a significant proportion among medical professionals engaged in research, though this contribution is less compared to students of other professions [1]. Research provides the students with an intellectually challenging, self-learning experience [2], and participating in research is important in producing doctors with an understanding of evidence-based medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Research provides the students with an intellectually challenging, self-learning experience [2], and participating in research is important in producing doctors with an understanding of evidence-based medicine. Participation in research and audits while in medical school can help develop these skills whilst prompting interest in academic pursuits [1]. …”
Section: Introductionmentioning
confidence: 99%